Kajian Morfologi Tanah Sambaran Petir Intensitas Tinggi - Muhammad Farhan Akil Bahri; La Ode Amaluddin; Rosliana Eso (Jurusan Pendidikan Geografi FKIP Universitas Halu Oleo, 2023)
Lightning is a dangerous natural phenomenon spreading electric charge from clouds in achieving success. The released charge takes the form of a lightning strike that causes an explosion at ground level. This study aims to describe the physical properties of the soil roughly in terms of (color, bulk density, porosity, texture, structure, pH, and soil moisture) and to describe the physical properties of the soil subtly using SEM (Scanning Electron Microscope) analysis to see the soil diameter and size. soil pores on soil exposed to high-intensity lighting in Sambuli and Purirano villages, Kendari City. This study uses a survey method. At each location, two points were taken, namely soil samples that were struck by high-intensity lightning and soil samples that were not struck by lightning to see changes caused by lightning. The method of measuring physical properties of the soil is measured by a method based on each sample of the physical properties of the soil to see the rough morphology and the Scanning Electron Microscope (SEM) test to see the fine morphology. The results of this study indicate that. Physical properties of high-intensity lightning strike soil in the form of a texture dominated by dusty clay texture has a granular and sub-angular blocky structure, has a bulk density value of 1.41 gr/cm3 – 1.89 gr/cm3 and 1.41 gr/cm3 – 1.74 gr/cm3, has wet soil moisture. Soil color at both locations seen vertically shows a dark color on the surface layer. Has a porosity of 0.470 % - 0.288 % and 0.47% - 0.343 %. The SEM test results showed that the soil particle size was dominated by macropore size with a very fine category. It has an average diameter of 270 μm and 1075 μm.